2006
DOI: 10.3998/ark.5550190.0008.912
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical constituents of Vangueria infausta: their radical scavenging and antimicrobial activities

Abstract: A new biflavonoid, 5,7,3',5'',7'',4'''-hexahydroxy (4'-O-3''')-biflavone (1) and a polyketide derivative, methylcylohex-1-ene (3) [previously reported only as a synthetic compound] were isolated from aerial parts of Vangueria infausta. In addition, eight other known flavonoids viz. (-)-epicatechin, epiafzelechin, dihydrokaempferol, quercetin, luteolin (2), dihydroquercetin-3'-Oglucoside, daidzein and genistein were also isolated from this plant. Structures were identified using 1D-and 2D NMR experiments as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…60,61 Mbukwa et al isolated the new biavonoid 5,7,3 0 ,5 00 ,7 00 ,4 000 -hexahydroxy(4 0 -O-3 000 )-biavone (31) together with the known compounds (À)-epicatechin (20), epiafzelechin (32), dihydrokaempferol (33), quercetin (34), luteolin (35), dihydroquercetin-3 0 -O-glucoside (36), daidzein (37) and genistein (38) from aerial parts of Vangueria infausta (Rubiaceae). 62 Compound 31 showed higher radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) reagent compared to ascorbic acid (standard) using a spectrophotometric method. But compound 31 was less sensitive to Grampositive and Gram-negative bacterial strains and yeast (Candida mycoderma) compared to 34 and 35 on the Bioautographic Agar Overlay Assay.…”
Section: Flavonoids From Southern African Floramentioning
confidence: 99%
See 1 more Smart Citation
“…60,61 Mbukwa et al isolated the new biavonoid 5,7,3 0 ,5 00 ,7 00 ,4 000 -hexahydroxy(4 0 -O-3 000 )-biavone (31) together with the known compounds (À)-epicatechin (20), epiafzelechin (32), dihydrokaempferol (33), quercetin (34), luteolin (35), dihydroquercetin-3 0 -O-glucoside (36), daidzein (37) and genistein (38) from aerial parts of Vangueria infausta (Rubiaceae). 62 Compound 31 showed higher radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) reagent compared to ascorbic acid (standard) using a spectrophotometric method. But compound 31 was less sensitive to Grampositive and Gram-negative bacterial strains and yeast (Candida mycoderma) compared to 34 and 35 on the Bioautographic Agar Overlay Assay.…”
Section: Flavonoids From Southern African Floramentioning
confidence: 99%
“…90 Ultra-high performance liquid chromatography coupled to mass spectrometry (UHPLC-MS) was investigated as an ultrafast, accurate, and sensitive method in the quantication of the main compounds in 101 Aloe ferox exudates, harvested in South Africa. 91 The main compounds were shown to be the chromones; aloeresin A (59), aloesin (60) and the anthrones aloin A (61) and aloin B (62). Even though the identied compounds have not been tested, this plant is known to possess laxative and cathartic effects.…”
Section: Quinones From Southern African Floramentioning
confidence: 99%
“…Leaves and branches extracts of this plant exhibited no cytotoxicity against HepG2 cells at the final concentration of 100 µg/mL [58], while another study showed antiproliferative activity of a methanolic branch extract with an LC 50 of 37 µg/mL, 72 µg/mL, 43 µg/mL, and 20 µg/mL against MCF-7, HCT-116, HepG2, and A-549, respectively [59]. A study showing the antioxidant effect of D. caffra fruit extract against free radicals showed that the whole fruit extract's DPPH scavenging action peaked at 52.11% (IC 50 95.09 µg/mL) at a concentration of 100 µg/mL, while the flesh extract's action was 27.11% (IC 50 187.12 µg/mL) at the same concentration. The two main phenolic compounds in dry fruits that were identified were chlorogenic, pyrogallol, and malic acids as the most prevalent organic acids.…”
Section: Kei Applementioning
confidence: 99%
“…Wild medlar has been utilized to treat roundworm, snake bites, malaria, fever, fungal infections (candidiasis), pneumonia, and chest-related problems in traditional medicine [ 56 , 88 , 92 ]. The successful use of wild medlar in traditional medicine can be traced back to its antioxidant, antibacterial, antifungal, antiplasmodial, and anti-inflammatory properties [ 88 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. The cytotoxicity activities of methanolic and aqueous root extracts of this plant against MAGI CC5+ cells showed cytotoxic half-maximal concentrations (CC50) of 0.1 mg/mL [ 101 ].…”
Section: Fruits In Cancer Treatmentmentioning
confidence: 99%